2015
DOI: 10.1371/journal.pone.0128673
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Lamivudine for Chemotherapy-Induced Hepatitis B Reactivation in Breast Cancer: A Meta-Analysis

Abstract: BackgroundThree strategies using lamivudine have been proposed to prevent chemotherapy-induced HBV (hepatitis B virus) reactivation in the clinical setting. The purpose of this meta-analysis is to evaluate the efficacy of the early preemptive strategy, deferred preemptive strategy and therapeutic strategy in patients with HBsAg-positive breast cancer during chemotherapy.MethodsClinical studies published from database inception until Nov 1, 2014, were included for analysis. The primary outcomes were overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Several inconsistencies were found in the incidence of HBV reactivation, HBV-associated hepatitis and disruption of chemotherapy between the prophylactic lamivudine group and non-prophylaxis group. As for patients with solid tumours, three meta-analysis Tang et al, 2015;Zheng et al, 2013) have investigated the efficacy of prophylactic lamivudine in patients with breast cancer and another two (Hicks LK et al, 2016;Paul et al, 2016) This study demonstrated that prophylactic lamivudine in HBsAgseropositive patient with solid tumours undergoing chemotherapy effectively reduces HBV reactivation (p < .00001) and its consequent negative outcomes, including hepatitis (p < .00001), disruption of chemotherapy (p = .01) and mortality (p = .08). However, one prospective RCT (Long et al, 2011) suggested the incidence of hepatitis, chemotherapy disruptions and overall death between the prophylactic lamivudine group and non-prophylaxis group were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several inconsistencies were found in the incidence of HBV reactivation, HBV-associated hepatitis and disruption of chemotherapy between the prophylactic lamivudine group and non-prophylaxis group. As for patients with solid tumours, three meta-analysis Tang et al, 2015;Zheng et al, 2013) have investigated the efficacy of prophylactic lamivudine in patients with breast cancer and another two (Hicks LK et al, 2016;Paul et al, 2016) This study demonstrated that prophylactic lamivudine in HBsAgseropositive patient with solid tumours undergoing chemotherapy effectively reduces HBV reactivation (p < .00001) and its consequent negative outcomes, including hepatitis (p < .00001), disruption of chemotherapy (p = .01) and mortality (p = .08). However, one prospective RCT (Long et al, 2011) suggested the incidence of hepatitis, chemotherapy disruptions and overall death between the prophylactic lamivudine group and non-prophylaxis group were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…However, these articles either focused on haematological tumours or mixed solid and haematological malignancy together. As for patients with solid tumours, three meta-analysis Tang et al, 2015;Zheng et al, 2013) have investigated the efficacy of prophylactic lamivudine in patients with breast cancer and another two (Hicks LK et al, 2016;Paul et al, 2016) This study demonstrated that prophylactic lamivudine in HBsAgseropositive patient with solid tumours undergoing chemotherapy effectively reduces HBV reactivation (p < .00001) and its consequent negative outcomes, including hepatitis (p < .00001), disruption of chemotherapy (p = .01) and mortality (p = .08). A total of 10 HBV-related deaths were reported in some of our incorporated studies (Dai et al, 2004;Lee et al, 2012;Lim et al, 2002;Lin et al, 2014;Yeo et al, 2005) with mortalities ranging from 0% to 20% and all the deaths came from the group without lamivudine…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to recent studies, the intervention strategies can be divided into as follows: (i) prophylactic therapy (early pre‐emptive therapy): use of antivirals prior to the start of chemotherapy; (ii) pre‐emptive therapy (deferred pre‐emptive therapy): test HBV DNA regularly and use antivirals immediately when HBV DNA rises above baseline and ALT level is still within normal limits; (iii) therapeutic intervention: use antivirals when ALT level rises . Recent meta‐analyses have addressed the efficacy of pre‐emptive therapy for HBV reactivation in patients with breast cancer . We also performed a meta‐analysis to assess the benefits of prophylactic lamivudine for reactivation by adding more data.…”
Section: Introductionmentioning
confidence: 99%